ANALISIS SUPLLY CHAIN DAN KEUNTUNGAN INDUSTRI KACANG GOYANG UD. SERASI KOTAMOBAGU - ADITYA . MERTA (Universitas Sam Ratulangi, 2012)
The purpose of this study is to identity the suplly chain and to analyze the benefits on industry kacang goyang In UD. Serasi, and trough research is expected to profide the information for owners and people who need it. From this research can seen that UD. Serasi was suplly their raw materials for kacang goyang production like a ground nut, sugar, and chocolate powder directly from distributor, in this case middleman or store. Suplly chain suppose be in configuration model, and be related and continuous, but in UD. Serasi suplly chain only to the distributor who selling raw materials. Thereâ€™ no partnership between peanut farmer with UD. Serasi so that couse in frequent matching exhausted suplly of commonly supllied distributor. For the large presentation cost pesentage is variable cost 93,53Â %, where as fix cost only 6,48 %. On production system, industry kacang goyang in UD. Serasi get benefit Rp. 13.599.587. So the conclution, suplly chain kacang goyang in UD. Serasi was relative inefficient. Demand of raw materials were adjusted to the necessary, so that couse frequent occurrence of exhausted suplly due to the many demand, especially on the feast day.